Climate-Smart Agriculture Implementation Brief : A Summary of Insights and Upscaling Opportunities through the Africa Climate Business Plan - World Bank (World Bank, Washington, DC, 2020)
African countries are adopting a range of context-specific climate-smart technologies and practices to meet their food security and climate change goals. Improved livestock production is the most prevalent practice, followed by improved water management, conservation agriculture, agroforestry, and, notably, digital agriculture. The application of digital technology in the design and delivery of integrated weather and market advisories using big data analytics is increasingly helping countries identify conditions that may endanger food security and inform farmers’ decisions to adequately respond to and, when possible, capitalize on, the changing conditions.